Resilience of unaccompanied refugee children in foster care at Tongogara Refugee Camp Zimbabwe - Witness Chikoko; Johanne Mhlanga; Kudzai Mwapaura (Discover Global Society)
Abstract This article explores and discusses the resilience of refugee children under foster care in Zimbabwe. It advances the argument that there are resilience factors associated with unaccompanied refugee children under the foster care programme at the Tongogara Refugee Camp. Data were gathered using an exploratory qualitative research design using document analyses, 10 refugee children under foster care and 10 key informant interviews, which were conducted to gain a deeper understanding of the lives of refugee children under foster care at the Tongogara Refugee Camp. Evidence from the sources shows that there are several factors enhancing resilience among unaccompanied minors in foster care, such as religious, personal and macro support from foster parents, agencies involved in childcare, and educational support. It is recommended that the National Orphan Care Policy of 1999 be reviewed and the provisions of social protection programmes for unaccompanied refugee children under foster care be strengthened.